Height and cancer incidence in the Million Women Study: prospective cohort, and meta-analysis of prospective studies of height and total cancer risk - Green, J; Cairns, B; Casabonne, D; Wright, F; Reeves, G; Beral, V (2011)
Background: Epidemiological studies have shown that taller people are at increased risk of cancer, but it is unclear if height-associated risks vary by cancer site, or by other factors such as smoking and socioeconomic status. Our aim was to investigate these associations in a large UK prospective cohort with sufficient information on incident cancer to allow direct comparison of height-associated risk across cancer sites and in relation to major potential confounding and modifying factors. Methods: Information on height and other factors relevant for cancer was obtained in 1996-2001 for middle-aged women without previous cancer who were followed up for cancer incidence. We used Cox regression models to calculate adjusted relative risks (RRs) per 10 cm increase in measured height for total incident cancer and for 17 specific cancer sites, taking attained age as the underlying time variable. We also did a meta-analysis of published results from prospective studies of total cancer risk in relation to height. Findings: 1 297 124 women included in our analysis were followed up for a total of 11·7 million person-years (median 9·4 years per woman, IQR 8·4-10·2), during which time 97 376 incident cancers occurred. The RR for total cancer was of 1·16 (95% CI 1·14-1·17; p<0·0001) for every 10 cm increase in height. Risk increased for 15 of the 17 cancer sites we assessed, and was statistically significant for ten sites: colon (RR per 10 cm increase in height 1·25, 95% CI 1·19-1·30), rectum (1·14, 1·07-1·22), malignant melanoma (1·32, 1·24-1·40), breast (1·17, 1·15-1·19), endometrium (1·19, 1·13-1·24), ovary (1·17, 1·11-1·23), kidney (1·29, 1·19-1·41), CNS (1·20, 1·12-1·29), non-Hodgkin lymphoma (1·21, 1·14-1·29), and leukaemia (1·26, 1·15-1·38). The increase in total cancer RR per 10 cm increase in height did not vary significantly by socioeconomic status or by ten other personal characteristics we assessed, but was significantly lower in current than in never smokers (p<0·0001). In current smokers, smoking-related cancers were not as strongly related to height as were other cancers (RR per 10 cm increase in height 1·05, 95% CI 1·01-1·09, and 1·17, 1·13-1·22, respectively; p=0·0004). In a meta-analysis of our study and ten other prospective studies, height-associated RRs for total cancer showed little variation across Europe, North America, Australasia, and Asia. Interpretation: Cancer incidence increases with increasing adult height for most cancer sites. The relation between height and total cancer RR is similar in different populations. Funding: Cancer Research UK and the UK Medical Research Council. © 2011 Elsevier Ltd.